To leave or to settle? Kazuo Ishiguro’s remains of the summer in Nagasaki (Philologia, 2021)
In this article, by extending the Prague School linguists’ and M.A.K. Halliday’s notion of the theme–rheme sequence at clause level to the level of the entire ﬁctional text, I attempt to analyze the theme-rheme structure of Kazuo Ishigruo’s novels, concluding that his ‘discourse theme’ of LEAVING is ‘mediated’ and given a solution of SETTLING, or ‘discourse rheme’, in the end in his attempt to overcome cultural and ethnic differences he faces in Britain. Etsuko’s LEAVING Nagasaki is MEDIATED into her SETTLING in a new English hometown (A Pale View of Hills); Stevens’s LEAVING the old Manor is MEDIATED into his SETTLING in his ‘new’ Manor (The Remains of the Day). In the light of this structure, one can better appreciate the passage at the beginning of The Remains of the Day (“Why don’t you take the car and drive off somewhere for a few days?”). What is thematically important here is that Stevens’ returning to and remaining in the Manor is inter-textually implied in this phrase. After his ‘break in his new master’s car’, he returns there, though not to completely the same environment.
Keywords: literary discourse; discourse theme; discourse rheme; mediation; attenuation of change; functional